Structures of the wild-type MexAB–OprM tripartite pump reveal its complex formation and drug efflux mechanism - Kenta Tsutsumi (Nature Portfolio, 2019)
In Pseudomonas aeruginosa, MexAB–OprM plays a central role in multidrug resistance by ejecting various drug compounds. Here the authors present the structure of wild-type MexAB–OprM in the presence or absence of drugs and propose mechanisms for complex formation and drug efflux.